Apoptosis and apoptotic extracellular vesicular particles in atherogenesis - Yu. Sh. Shwartz; M. I. Chasovskikh; S. V. Cheresiz; M. V. Kruchinina (Атеросклероз, 2015)
The review summarizes current notions on the role of apoptosis and apoptotic cell-derived extracellular vesicles in atherogenesis. The mechanisms of efferocytosis impairment and its significance in atherosclerotic vulnerable plaque formation are discussed. The data on the pro- and anti-inflammatory effects of apoptotic extracellular vesicular particles are presented.